Tourism marketing a collaborative approach - Fyall Alan; Garrod Brian (New Delhi Viva Books, 2006)
This book provides a thorough and detailed understanding of tourism marketing principles and practice within the context of inter-organisational collaboration. It begins with an overview of existing marketing and strategic marketing theory and practice
Keywords: Tourism-marketing